Comparison of surgical morbidities between LigaSure™ and conventional techniques in inguinal or ilioinguinal lymph node dissection for skin cancer: A single center retrospective study. Issue 10 (27th June 2022) - Umeda, Yoshiyasu; Teramoto, Yukiko; Asami, Yuri; Matsuya, Taisuke; Saito, Shintaro; Sasaki, Katsuhito; Baba, Natsuki; Ishizuki, Shoichiro; Kamimura, Anna; Yamaguchi, Buntaro; Kawahara, Yu; Takai, Sayaka; et al.
Abstract: Skin cancer patients with clinical nodal disease or whose positive sentinel nodes had great tumor burden remain candidates for regional lymph node dissections. Among these patients, inguinal or ilioinguinal lymph node dissection is frequently required in clinical practice, which is associated with significant postoperative morbidity—including lymphatic leakage. The aim of this retrospective study was to evaluate the efficacy of LigaSure™, an electrothermal bipolar vessel sealing system, in reducing lymphatic leakage in inguinal or ilioinguinal lymph node dissection. In total, 58 patients who received inguinal or ilioinguinal lymph node dissection (conventional group, 48; LigaSure™ group, 10) and shared similar characteristics were included in this study. Lymphatic leakage after drain removal was significantly lower in the LigaSure™ group than that in the conventional group (present ratio, 0% vs. 37%; p = 0.02). The daily lymphatic drainage volume also tended to be lower in the LigaSure™ than that in the conventional group, with significant differences on postoperative day 1 ( p = 0.02). Other perioperative outcomes including the operating time, intraoperative blood loss, time to drain removal, duration of hospital stay, flap necrosis, and wound infection showed no significant differences between the two groups. The use of the LigaSure™ in inguinal or ilioinguinal lymph node dissection for the treatment of skin cancer could reduce the incidence of postoperative lymphatic leakage after drain removal.